CHARACTERISTICS OF PLASMA DEPOSITED TUNGSTEN SCHOTTKY CONTACTS TO GAAS - KIM, YT; LEE, CW; HAN, CW; HONG, JS; MIN, SK (AMER INST PHYSICS, 1992)
A low resistive tungsten (W) Schottky contact to GaAs has been developed by plasma enhanced chemical vapor deposition. The resistivity of tungsten (W) films deposited on GaAs at 300-degrees-C is about 18-mu-OMEGA cm and the film structure is (111) oriented alpha-phase W coexisting with (200) and (21 1 ) oriented beta-phase tungsten. The resistivity of W films deposited above 350-degrees-C is increased due to the diffusion of Ga and As atoms from GaAs into W films. This has been confirmed by secondary ion mass spectroscopy. I-V characteristics of GaAs Schottky contacts formed at 300-degrees-C show that the maximum barrier height is 0.81 eV and the ideality factor is 1.04. They are not degraded during rapid thermal annealing at temperatures ranging from 500 to 700-degrees-C for 10 s without an arsenic overpressure.
Keywords: THIN-FILMS; INTERFACE